PRODUCTION BRACHIARIA IN DEGRADED AREA RECOVERY USING SEWAGE SLUDGE AND MINERAL FERTILIZER - BONINI, Carolina dos Santos Batista; ALVES, Marlene Cristina; MARCHINI, Debora de Cássia; ARRUDA, Otton Garcia; NETO, Alfredo BONINI (Revista Brasileira de Engenharia de Biossistemas, 2010)
Land use does not always give rise to a new sustainable ecological system, whether crops or pastures. Thus, soils and intensively used improperly, are led to degradation. Techniques aimed at restoring degraded soils have been investigated. In this sense the present work was to study the influence of sewage sludge on a degraded soil in the development of eucalyptus (Eucalyptus citriodora Hook) being cultivated for three years and (Brachiaria decumbens) in the municipality of Selvíria, MS . The experimental design was a randomized block design with 4 treatments and 4 replications. The treatments were: control (no use of sewage sludge and mineral fertilizer); mineral fertilizer; 30 Mg ha-1 of sewage sludge; 60 Mg ha-1 of sewage sludge. Eucalyptus and palisadegrass street planting was grown. We assessed the development of eucalyptus (plant height and height of the fork 1st) and Brachiaria (green and dry mass). The results were analyzed by performing analysis of variance and Tukey test at 5% probability for comparison of means. There were positive effects of sewage sludge on plant development of eucalyptus and pasture.